A reduced two-layer non-hydrostatic model for submarine landslide-generated tsunamis. (October 2022) - Tarwidi, Dede; Pudjaprasetya, Sri Redjeki; Adytia, Didit
Abstract: The goal of this research is to develop an efficient numerical scheme for simulating the appearance of surface waves induced by submarine landslides. In this study, a reduced two-layer non-hydrostatic model is extended to include a time-varying solid bottom. This reduced two-layer non-hydrostatic scheme is computationally efficient, comparable to a one-layer scheme, but has the accuracy of a two-layer system. The accuracy and flexibility of the reduced two-layer non-hydrostatic scheme (abbreviated as NH-2LR) used here are explained by studying the dispersion relation. As benchmark tests, the NH-2LR model is validated using a variety of tsunami simulations generated by landslides, including impulsive vertical bottom motions, mass sliding on an inclined plane, and horizontal landslide motion. The numerical findings are shown to be in good agreement with the experimental observations, implying that the proposed model is a feasible alternative for modeling landslide-generated tsunamis. It is also shown that the new scheme reduces computational effort while maintaining high accuracy. Highlights: A dispersive model is developed and used to simulate waves generated by landslides. The model can describe dispersive waves in the range 0 < k d 0 < 7 . 7 within error ¡2%. The computational cost is similar to 1-layer model, accuracy close to 2-layer model. Validation against experiments and other numerical models has shown good agreements.